El acompañamiento docente en la motivación en Educación Básica Superior - Pinduisaca Yungan, Brissel Anahis (2025)
The goal of this research is to analyze teacher support in motivating upper elementary students at "Fe y Alegría" Elementary School. This work is essential for promoting active participation and both academic and emotional development. Teacher support should be constant, empathetic, and personalized to strengthen learning. Teachers' roles extend beyond teaching content to fostering students' overall development by adapting to their needs and creating a climate of trust. The study employs a mixed-methods approach, combining quantitative analysis of student surveys and qualitative observation of teachers' practices. The research design is non-experimental, consisting of descriptive, exploratory, basic, field, bibliographic, and cross-sectional studies. The sample consists of eighth-grade teachers and students, who completed the relevant data collection instruments. Results indicate that student motivation is moderate, influenced by both internal and external factors. Some teachers use feedback, varied resources, and recognize effort, but these actions are not enough to sustain motivation. Thus, there is a need to consistently and in context strengthen teacher support. In conclusion, limitations persist in utilizing innovative strategies for active, participatory, and student-centered learning. The solution is to implement new strategies that boost student motivation, taking into account emotions, interests, autonomy, and individual needs.